Is the nursing process part of quality care? (2010)
The main purpose of this article is to answer the question: Is the nursing process part of quality care? In order to back the answer, it starts by mentioning several authors that have performed studies on the use of scientific methods, problem solving methods and the attention to care -innursing method and its relationship to the quality of service and the nursing care, while at the same time it introduces related experiences associated with NIPE research projects and related Groups with Dx, and evaluation experiences for nursing services in various homes and hospitals in Colombia, México, Cuba and Chile. There, one can appreciate that the nursing process is that which is defined by the concept of applied nurse. It concludes that by saying that the nursing process is fundamental to nursing care, because it shortens distances, reduces the number of complications and avoids risks, while contributing to improve the quality of service and the quality of life of patients /users.